Development of Islamic Accounting Theory: Integrating Tawhid, Maqashid al-Shariah, and Islamic Ethics into the Accounting System - Saputra, Wali (Indo Publishing, 2025)
This study aims to develop an Islamic Accounting Theory (IAT) as a conceptual framework that integrates the principles of tawhid, maqashid al-shariah, and Islamic ethics into accounting systems. Using an exploratory qualitative approach through library research and grounded theory, this research reviews relevant academic literature and conducts in-depth interviews with experts in Islamic accounting. The findings indicate that Islamic accounting rests on three core pillars: (1) The Ontology of Tawhid, which positions accounting as an act of worship and trust (amanah); (2) The Epistemology of Shariah, derived from divine revelation and scholarly ijtihad; and (3) The Axiology of Maqashid al-Shariah, which emphasizes social justice, transparency, and collective well-being. This research contributes to the development of a new paradigm in accounting by affirming that Islamic financial reporting is not merely economic in nature, but also spiritual, moral, and social. The implications include designing Islamic accounting curricula, developing maqashid-based reporting standards, and strengthening comprehensive shariah audit policies.